Imagining Muslims in South Asia and the diaspora secularism, religion, representations - Chambers, Claire, 1975-; Herbert, Caroline (New York, New York : Routledge, 2015)
'Literary, cinematic and media representations of the disputed category of the'South Asian Muslim' have undergone substantial change in the last few decades and in particular since the events of September 11, 2001. Here we find the first book-length critical analysis of these representations of Muslims from South Asia and its diaspora in literature, the media, culture and cinema. Contributors contextualize these depictions against the burgeoning post-9/11 artistic interest in Islam, and also against cultural responses to earlier crises on the subcontinent such as the Partition, the 1971 Indo-Pakistan war and secession of Bangladesh, the 1992 Ayodhya riots , the 2002 Gujarat genocide and the Kashmir conflict. Offering a comparative approach, the book explores connections between artists' generic experimentalism and their interpretations of life as Muslims in South Asia and its diaspora, exploring literary and popular fiction, memoir, poetry, news media, and film. The collected essays highlight the significant role that literature, film, and other cultural products such as music can play in opening up space for complex reflections on Muslim identities and cultures, and how such imaginative cultural forms can enable us to rethink secularism and religion. Surveying a broad range of up-to-date writing and cultural production, this concise and pioneering critical analysis of representations of South Asian Muslims will be of interest to students and academics of a variety of subjects including Asian Studies, Literary Studies, Media Studies, Women's Studies, Contemporary Politics, Migration History, Film studies, and Cultural Studies'--
pt. 1. Surveying the field : comparative approaches -- pt. 2. Syncretism, Muslim cosmopolitanism, and secularism -- pt. 3. Currents within South Asian Islam -- pt. 4. Representations, stereotypes, Islamophobia.
Includes bibliographical references and index.
Also available in print edition.
Mode of access: World Wide Web.
Keywords: South Asian literature -- 20th century -- History and criticism; South Asian literature -- 21st century -- History and criticism; Muslims in literature; Muslims -- South Asia; Electronic books